2016
DOI: 10.7224/1537-2073.2015-031
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Multiple Sclerosis Scale

Abstract: Background: The Coping with Multiple Sclerosis Scale (CMSS) was developed to assess coping strategies specific to multiple sclerosis (MS). Despite its wide application in MS research, psychometric support for the CMSS remains limited to the initial factor analytic investigation by Pakenham in 2001. Methods: The current investigation assessed the factor structure and construct validity of the CMSS. Participants with MS (N = 453) completed the CMSS, as well as measures of disability related to MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In general, the results of most studies have identified that the emotion-focused strategy is the most important mediator of the relationship between stress and disease (29). The emotion-focused strategy is known as a shortterm strategy, yet in the long term it can inhibit psychological adaptation and cause psychiatric disorders, such as depression (6,30).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the results of most studies have identified that the emotion-focused strategy is the most important mediator of the relationship between stress and disease (29). The emotion-focused strategy is known as a shortterm strategy, yet in the long term it can inhibit psychological adaptation and cause psychiatric disorders, such as depression (6,30).…”
Section: Discussionmentioning
confidence: 99%